EFFECT OF KAOLIN ON HISTOPATHOLOGICAL ALTERATIONS IN CYPRINUS CARPIO CHALLENGED WITH PSEUDOMONAS AERUGINOSA - Noor M. Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to assess the role of kaolin in reducing the adverse effect of Pseudomonas aeruginosain common carp, Cyprinus carpio. Specifically, the histopathological alterations in kidney, spleen and liver were investigated. Firstly, P. aeruginosa was isolated from infected fish. A total of 100 fish (40.8 ± 2 g)were divided into five groups in duplicate (10 fish in each replicate) as:control healthy (C-) group uninfected and without kaolin treatment; (C+): fish were infected with P. aeruginosa and without kaolin treatment. Group T1, T2 and T3 fish were infected experimentally with P. aeruginosa (LD50= 2±0.2×109 CFU ml-1), andtreated with kaolin at concentrations of 4, 6, 8 g/L for 7 successive days respectively.Kidney sections in positive control showedhydrobic degeneration, reduction of hemopotic tissue, and nuclear pyknosis. Spleen sectionsexhibited melanomacrophage aggregation and congestion in red bulb of the positive control. While, liver sections revealed necrosis of hepatic cells and cellular vacuolation. All of these alterations were lesser of extent in kidney, spleen and liver in kaolin treated groups. Overall, this study provides insights into the potential use of kaolin as a treatment for against P. aeruginosa in common carp and may contribute to the understanding of the mechanisms underlying histopathological alterations in response to bacterial infections. As well as, histopathological alterations provides detailed information and a powerful tool about the cellular and subcellular structure of tissues and organs.